International Labor Migration and Its Socioeconomic Consequences for Rural Communities: A Case Study of Pakong District, Indonesia - Sofiatun Imamah; Abd. Hamid (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the driving factors of international labor migration and its impact on the socio-economic conditions of migrant households in Pakong District, Pamekasan Regency. Socio-economic conditions in this study are operationalized through indicators of household income, ownership of productive and consumptive assets, continuity of children's education, and housing quality . The study used a qualitative approach with purposive and snowball sampling techniques , involving 15 informants of international migrant workers in the informal sector working in Malaysia and Saudi Arabia with a minimum work period of one year. Data were collected through in-depth interviews and participant observation, then analyzed thematically. The results of the study indicate that migration is driven by structural pressures in the area of origin (limited employment opportunities and low levels of education) as well as economic attractions in the destination country in the form of relatively higher wages and established migrant networks. The positive impacts of migration are reflected in increased household income, improved housing quality, financing children's education, and increased family economic independence . However, migration also has negative impacts in the form of weakened family relations and reduced parental supervision of children . This study makes an empirical contribution by showing that international migration in rural Madura not only functions as a household economic strategy, but also shapes social transformations based on remittances and migrant networks , which have not been widely discussed in previous migration studies.